2021
DOI: 10.1002/mnfr.202100606
|View full text |Cite
|
Sign up to set email alerts
|

Food and Microbiota Metabolites Associate with Cognitive Decline in Older Subjects: A 12‐Year Prospective Study

Abstract: Scope: Diet is considered an important modulator of cognitive decline and dementia, but the available evidence is, however, still fragmented and often inconsistent. Methods and Results: The article studies the long-term prospective Three-City Cohort, which consists of two separate nested case-control sample sets from different geographic regions (Bordeaux, n = 418; Dijon, n = 424). Cognitive decline is evaluated through five neuropsychological tests (Mini-Mental State Examination, Benton Visual Retention Test,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 49 publications
(62 reference statements)
2
14
0
Order By: Relevance
“…In turn, FFAs are thought to participate in the pathogenesis of AD by stimulating the assembly of amyloid plaques and tau filaments [ 25 ], as well as by inducing inflammation and insulin resistance [ 26 ]. In agreement with recent studies, we furthermore found increased levels of various ACs among CD cases [ 27 31 ], suggestive of incomplete fatty acid β-oxidation. A large body of evidence has demonstrated that glucose hypometabolism is a primary hallmark of CD, AD and other neurodegenerative disorders, which starts decades before the onset of clinical symptoms [ 2 ].…”
Section: Discussionsupporting
confidence: 93%
“…In turn, FFAs are thought to participate in the pathogenesis of AD by stimulating the assembly of amyloid plaques and tau filaments [ 25 ], as well as by inducing inflammation and insulin resistance [ 26 ]. In agreement with recent studies, we furthermore found increased levels of various ACs among CD cases [ 27 31 ], suggestive of incomplete fatty acid β-oxidation. A large body of evidence has demonstrated that glucose hypometabolism is a primary hallmark of CD, AD and other neurodegenerative disorders, which starts decades before the onset of clinical symptoms [ 2 ].…”
Section: Discussionsupporting
confidence: 93%
“…Similar changes in inflammatory lipid species have also been found in Parkinson's disease [43] and Multiple sclerosis [44], as well as metabolic diseases such as type 2 diabetes [45], non-alcoholic steatohepatitis [46] and non-alcoholic fatty liver [47] where liver biopsies and high serum levels of sphingomyelins have been used as biomarkers of visceral adipose tissue and hepatic triglyceride content [47,48]. A protective association between metabolites reflecting the consumption of mushroom and brain health have been proposed in a prospective cognitive decline study with humans [18] and after oral administration of the mushroom derived antioxidant ergothioneine in a recognition memory study in rodents [17]. This information provides additional evidence for improved mental health through diets that alter the gut microbiome to positively interact with the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Edible mushroom derived proteins lectins [2], amino acid ergothioneine [4], flavonoids [5] and polysaccharides categorized as glucans with β-type glycosidic bonds have been proposed as bioactive components responsible for regulation of the gut microbiome, modulation of the host immune response, hypolipidemic and anti-oxidant activity [6][7][8][9][10][11]. In addition, neuroprotective and antiageing properties of mushroom and isolated compounds like ergothioneine have been proposed for use against age related disorders [12][13][14][15][16][17][18], through the anti-inflammatory action purportedly regulated by changes in the composition of the intestinal microbiome. However, more preclinical evidence is required to understand the potential mechanism of action of dietary mushroom in treatment or neurological disease prevention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No specific deficiency disease has yet been identified for ET, which makes it hard to formally classify it as a vitamin. Perhaps, however, deficiency diseases are staring us in the face: low blood or plasma levels of ET are correlated with increased risk of frailty [16][17][18], cardiovascular disease [19], mild cognitive impairment [18,[20][21][22], dementia [22,23] and Parkinson's disease [24]. Indeed, ET has many neuroprotective properties [4,5,18,26,27], as reviewed in detail in this special issue [18,25,26].…”
mentioning
confidence: 99%